Short Run Gravity - James E. Anderson; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2017)
Short run gravity is a geometric weighted average of long run gravity and bilateral capacity. The model features (i) joint trade costs endogenous to bilateral volumes, (ii) long run gravity as a limiting case of effcient investment in bilateral capacities, (iii) a structural ratio of short run to long run trade elasticities equal to a microfounded buyers' incidence elasticity, and (iv) tractable short and long run models of the extensive margin. Application to manufacturing trade of 52 countries during the globalization period 1988-2006 strongly supports the model. Results solve several time invariance and trade elasticity puzzles in the literature.
Keywords: F13; F14; F16; 330; trade elasticity puzzles; export dynamics; missing globalization